PERINATAL OUTCOMES AND PROGNOSTIC FACTORS IN EARLY AND LATE-ONSET FETAL GROWTH RESTRICTION - Rıza Madazlı; Verda Alpay; Didem Kaymak; İpek Betül Özçivit (İstanbul Tıp Fakültesi Dergisi)
Objective: To evaluate the obstetric and perinatal outcomes of fetuses with early (EO) and late-onset (LO) fetal growth restriction (FGR), and to explore the prognostic factors on perinatal survival and adverse perinatal outcome. Materials and Methods: We retrospectively reviewed 105 EO and 55 LO-FGR singleton pregnancies. Umbilical artery (UA), middle cerebral artery (MCA) and ductus venosus (DV) Doppler parameters and cerebroplacental ratio (CPR) were assessed. Prognostic significance of gestational age at delivery, birth weight and Doppler parameters were evaluated. Results: Gestational age at delivery greater than 27 weeks (sensitivity 87.5%, specificity 76%) and birth weight of 665 g (sensitivity 88.8%, specificity 92%) provided the best prediction of survival in EO-FGR. Logistic regression analysis of UA absent or reversed end diastolic flow (EDF), abnormal DV Doppler, and absent/reversed DV a-wave revealed Odds Ratios of 2.57, 6.97, 4.51 and 8.75 respectively for perinatal mortality in EO-FGR. The incidence of CPR below the 5th percentile was significantly higher in LO-FGR pregnancies with the composite adverse outcome than normal outcome (p<0.001). Conclusion: Gestational age at delivery and birth weight are the strongest predictors of perinatal mortality in EO-FGR. In LOFGR, CPR <5th percentile is associated with an increased risk of delivery complications.